From anger to action: Differential impacts of eco-anxiety, eco-depression, and eco-anger on climate action and wellbeing - Samantha K. Stanley; Teaghan L. Hogg; Zoe Leviston; Iain Walker (Elsevier, 2021)
Research documents the experiences of depression and anxiety evoked by climate change, but little attention has been given to frustration and anger, or to untangling the effects of different emotional responses to the climate crisis on human and planetary health. Using Australian national survey data, we found that experiencing eco-anger predicted better mental health outcomes, as well as greater engagement in pro-climate activism and personal behaviours. Eco-anxiety and eco-depression were less adaptive, relating to lower wellbeing. Interestingly, those feeling eco-depressed were more likely to report participating in collective climate action, while those feeling eco-anxious were less likely to join the cause. Our findings implicate anger as a key adaptive emotional driver of engagement with the climate crisis, and prompt warnings about the mental health of populations increasingly worried and miserable about climate change.